REVITALISASI CERITA PANJI DALAM WAYANG BEBER - Rahmawati, Femi Eka (Studi Budaya Nusantara, 2018)
Abstract "Panji Stories" is one of East Java's Treasures. These stories had been spreadedall over the world in the form of various legends. Besides, these stories were also adapted by the caracters in many "Wayang" stories, one of them is Wayang Beber. Wayang Beber is one of the oldest Wayang in Indonesia and and it was developed in Java. It was a uniq wayang since it was performed by showing every scene in a background (dibeber in Javanis language), now days it will be almost the same as picture series in comics. The visualization of this wayang beber is exactly the same as the visualization of the stories in the two dimentions sculptures of temples in East Java. Panji Stories revitalization provides philosophy values and high historical values. Therefore, by applaying those story in Wayang Beber, it will be a way to conserve Indonesian's culture and a way to filter the expantion of foreign culture. In sum, wayang beber becomes cultural manifestation to deliver cultural and historical values from Panji Stories for young generation.